Erratum : Kinetic Study & Statistical Modelling of Sarawak Peat Water Electrocoagulation System using Copper and Aluminium Electrodes - Nazeri, Abdul Rahman; Nurhidayah Kumar, Muhammad Firdaus Kumar; Umang Jata, Gilan; Elisa Elizebeth, Jihed; Adarsh, Philip; Allene Albania, Linus; Dasima, Nen @ Shahinan.
In the article “Kinetic Study & Statistical Modelling of Sarawak Peat Water Electrocoagulation System using Copper and Aluminium Electrodes” by Nazeri Abdul Rahman, Nurhidayah Kumar Muhammad Firdaus Kumar, Umang Jata Gilan, Elisa Elizebeth Jihed, Adarsh Phillip, Allene Albania Linus, Dasima Nen@Shahinan, and Verawaty Ismail (Journal of Applied Science & Process Engineering, 2020, Vol 7, No. 1, pp 439–456. https://doi.org/10.33736/jaspe.2195.2020), there was an error in the Manuscript History. The stated history noted that the manuscript was received on 29 April 2020. The receipt date of the manuscript should have been stated as 9 April 2020.